The Influence of Price Discounts, Product Displays, and Product Quality on Impulsive Buying Behavior at Starbucks Coffee, Transmart Kawanua Manado Branch - Farelio Josua Massie; Djurwati Soepeno; Raymond Christian Kawet (International Journal of Economics Accounting and Management, 2024)
One business place that not only serves coffee, but also various drinks and food is a coffee shop. In this modern era, coffee shops have become part of the lifestyle in big cities around the world, where they have become a comfortable place to relax and gather. This research aims to understand the influence of price cuts, product displays and product quality on impulse buying behavior at Starbucks Coffee Transmart Kawanua Manado branch. The research method used is quantitative with a sampling technique using random purposive sampling. Data was collected through questionnaires distributed to 100 Starbucks Coffee Transmart Kawanua Manado consumer respondents, and analyzed using multiple linear regression with the help of SPSS version 25.0 software. The research results show that price discounts, product displays and product quality simultaneously influence impulse buying behavior at Starbucks Coffee Transmart Kawanua Manado Branch. Partially, Price Discounts and Product Quality have a positive and significant effect on impulse buying behavior, while Product Display does not have a significant effect. These findings provide a deeper understanding of the factors that influence impulse buying behavior in coffee shops, thereby providing valuable insights for marketing practitioners in managing promotional and sales strategies